(untitled) (Argumentum, 2017)
The research object of this article deals with a sharp ideological conflict that is associated with the presence of diametrically opposite interpretations of the nature of and the relevant interpretations of the present stage of socio-political crisis in Ukraine, which has started in 2013. In the mass media and in political literature, there is a wide range of characteristics and conceptual designations of the events of autumn 2013 – spring 2014 (and the subsequent processes) that vary from the “revolution of dignity” combined with the opposing her “foreign intervention” and “separatist movements” to a “coup d’etat” which provoked a “civil war” and “regionalist movements”. The objectives of the article are to show the limitations of one-dimensional, strikingly ideologized interpretations and the need (for social sciences) to generate unbiased multi-dimensional, multi-level vision of complex, contradictory, and, in fact, tectonic transformations in the contemporary Ukraine.